Survival and complications after neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy for locally advanced gastric cancer: a systematic review and meta-analysis - Zhu, Youqi; Chen, Jiuzhou; Sun, Xueqing; Lou, Yufei; Fang, Miao; Zhou, Fengjuan; Zhang, Lei; Xin, Yong (Frontiers in Oncology, 2023)
Background There is increasing evidence that neoadjuvant chemoradiotherapy is superior to neoadjuvant chemotherapy for patients with locally advanced gastric cancer. However, a number of studies have come to the opposite conclusion. Therefore, our meta-analysis is to evaluate the efficacy and safety of neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy in the treatment of locally advanced gastric cancer. Methods We searched Wanfang Database, China National Knowledge Network database, VIP database, China Biomedical Literature Database, PubMed, Embase and Cochrane Library. The searched terms included’Stomach Neoplasms’, ‘Neoadjuvant Therapy’ and ‘Chemoradiotherapy’. The retrieval time was from the establishment of the corresponding database to September 2022, and our meta-analysis was performed using RevMan (version 5.3) and Stata (version 17) software. Results A total of 17 literatures were included, which involved 7 randomized controlled trials and 10 retrospective studies, with a total of 6831 patients. The results of meta-analysis showed that compared with NACT group, the complete response rate(RR=1.95, 95%CI 1.39-2.73, p=0.0001), the partial response rate(RR=1.44, 95%CI 1.22-1.71, p=0.0001), the objective response rate(RR=1.37, 95%CI 1.27-1.54, p=0.00001), the pathologic complete response rate(RR=3.39, 95%CI 2.17-5.30, p=0.00001), the R0 resection rate(RR=1.18, 95%CI 1.09-1.29, p=0.0001) and 3-year overall survival rate(HR=0.89, 95%CI 0.82-0.96, p=0.002) of neoadjuvant chemoradiotherapy group were significantly improved. The results of subgroup analyses of gastric cancer subgroup and gastroesophageal junction cancer subgroup were consistent with the overall results. Meanwhile, the stable disease(RR=0.59, 95%CI:0.44-0.81, P=0.0010) of neoadjuvant chemoradiotherapy group was lower than that of neoadjuvant chemotherapy group, and there were no statistical significance in the progressive disease rate(RR=0.57, 95%CI:0.31-1.03, P=0.06), five-year overall survival rate(HR=1.03, 95%CI:0.99-1.07, P=0.839), postoperative complications and adverse reactions between the neoadjuvant chemoradiotherapy group and neoadjuvant chemotherapy group. Conclusion Compared with neoadjuvant chemotherapy, neoadjuvant chemoradiotherapy might bring more survival benefits without significantly increasing adverse reactions. neoadjuvant chemoradiotherapy may be a recommended treatment for patients with locally advanced gastric cancer. Systematic Review Registration https://inplasy.com/inplasy-2022-12-0068/, identifier INPLASY202212068.